2022
DOI: 10.1007/s00167-021-06851-x
|View full text |Cite
|
Sign up to set email alerts
|

An individualized decision between physical therapy or surgery for patients with degenerative meniscal tears cannot be based on continuous treatment selection markers: a marker-by-treatment analysis of the ESCAPE study

Abstract: Purpose Marker-by-treatment analyses are promising new methods in internal medicine, but have not yet been implemented in orthopaedics. With this analysis, specific cut-off points may be obtained, that can potentially identify whether meniscal surgery or physical therapy is the superior intervention for an individual patient. This study aimed to introduce a novel approach in orthopaedic research to identify relevant treatment selection markers that affect treatment outcome following meniscal surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Previous studies investigated specific patient characteristics and combinations of characteristics to estimate treatment outcome and possible subgroups of patient who will benefit more from surgery compared with physical therapy. [31][32][33][34] However, none of these studies were able to find such a subgroup of patients. This finding is in line with ours, showing that physical therapy is noninferior to arthroscopic partial meniscectomy in patients with degenerative meniscal tears.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Previous studies investigated specific patient characteristics and combinations of characteristics to estimate treatment outcome and possible subgroups of patient who will benefit more from surgery compared with physical therapy. [31][32][33][34] However, none of these studies were able to find such a subgroup of patients. This finding is in line with ours, showing that physical therapy is noninferior to arthroscopic partial meniscectomy in patients with degenerative meniscal tears.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, we checked for confounding effects within our primary outcomes, and our adjusted analyses are in line with our primary unadjusted results. Previous studies investigated specific patient characteristics and combinations of characteristics to estimate treatment outcome and possible subgroups of patient who will benefit more from surgery compared with physical therapy . However, none of these studies were able to find such a subgroup of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although they investigated a number of preoperative factors, including patient demographics and knee-related symptoms, the predictive performance of the prognostic model was poor [ 21 ]. Noorduyn et al also found that there was no clear subgroup of patients who would benefit from either surgery or physical therapy for a degenerative meniscal tear [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies attempted to identify a subgroup of patients who could show particularly favorable surgical outcomes after APM [ 21 , 22 ]. If surgeons preoperatively distinguish between those who would benefit from APM and those who would not, unnecessary surgery could be avoided and the outcomes of APM will be improved.…”
Section: Introductionmentioning
confidence: 99%
“…In assessing the outcomes of medial MAT, degenerative tears that occur in the late postoperative period should be analyzed separately because such tears are often asymptomatic. 20,31 Degenerative graft tears would have to be evaluated in the long term to verify their effects on the MAT survivorship. The present study tried to investigate the association between the long-term survival rate of medial MAT and graft tears.…”
mentioning
confidence: 99%